Modern methods for endoscopic treatment of obstructive pulmonary diseases. (21st October 2015) - Andrychiewicz, Anna; Gorka, Karolina; Reid, Michal; Soja, Jerzy; Sladek, Krzysztof; Szczeklik, Wojciech
Abstract: Background : Despite modern medicine's greatest efforts, many patients suffering from chronic obstructive pulmonary disease (COPD) and asthma remain refractory to the best treatments available. Bronchoscopy is increasingly being used to explore new approaches for treating these diseases, and several new techniques have recently shown encouraging results. The purpose of this review will be to shed some light on these methods. Methods : We searched Pubmed and Embase for English language articles from 1995 to September 2014, as well as ongoing trials on ClinicalTrials.gov. The following prespecified terms were used to search for clinical trials and case reports from the past 20 years: "endoscopic treatment of COPD", "endobronchial valve", and "bronchial thermoplasty". Results and discussion : In search for new COPD treatments, several trials have assessed the efficacy of one-way valves and other conceptually similar techniques including biological sealants and thermal vapor ablation. These methods all operate within a similar paradigm where the intention is to maximize ventilation of the remaining healthy parts of the lung, and to minimize the use and the space occupied by the diseased lung tissue. Similarly, a new non-pharmacologic therapeutic approach in asthma, bronchial thermoplasty (BT), was recently approved for use in the United States for adults with severe disease. The goal is to reduce the mass of hypertrophied smooth muscle in the bronchi to decrease bronchoconstriction. Conclusion : Both BT and the bronchoscopic treatments for COPD have shown promising results in recent studies, suggesting the onset of a new direction in obstructive lung disease treatment.